Modeling turbo-expander systems. (February 2013) - Jelodar, Mehdi Taleshian; Rastegar, Hasan; Abyaneh, Hossein Askarian
Turbo-expander systems have long been used instead of regulators, but they have recently received attention as a driving medium for power electrical generators. These systems typically replace the regulator valves that reduce the gas pressure in gas distribution networks. As a generator, however, its turbine generates mechanical power that can be considered as a new source for dispersed generation. To study the dynamics of turbo-expander systems, we first introduce a detailed model that incorporates components such as the preheater, reheater, nozzle angle, and the turbine. This model is validated using empirical data collected from thermo-dynamic analysis. To be specific, we also investigated the effects of using a variable-angle nozzle versus a fixed-angle nozzle turbine. As an application in distribution networks, we looked into the use of turbo-expander driven generators as highly efficient components. The dynamic behavior and transient stability of such generators are thoroughly analyzed for disturbances in either mechanical or electrical parts using the proposed model.